ANALYSIS OF THE DATA QUALITY OF SERVICE TRANSACTION ON INDONESIA’S BALANCE OF PAYMENTS - Istiqomah, Aisyah; Mita, Aria Farah (LPPM STIE Muhammadiah Bandung, 2023)
This study aims to analyze the root causes of data quality problems in Foreign Exchange Reporting (LLD) as the primary data source used in the preparation of the Indonesian Balance of Payments (NPI), especially in service transactions. The research method used is qualitative with a case study approach. Data collection was carried out through interviews, observation, and document analysis. The results of the study concluded that the data quality problem of LLD reporting was data accuracy. The root causes of the data quality problem of LLD reporting come from both the internal and external sides of Bank Indonesia. The root causes from the internal side of Bank Indonesia are complex transaction purpose codes (STT), acceleration of the development of service transaction, and manual data accuracy checks. While the root causes of the data quality problem from the external side of Bank Indonesia is the routine mutation of frontliner employees of the reporting bank and the lack of training conducted by the Head Office of the reporting bank. To address the root of the problem, several strategies are recommended to be implemented, namely adjustments to the STT list, training to LLD Account Officers, preparation of automated data accuracy check tools, preparation of e-learning and handbook about LLD reporting, as well as additional policies related to training obligations by Head Office of the reporting bank.